Shrinking the lymphatic filariasis map of Zimbabwe: Reassessing the population requiring treatment through confirmatory mapping - Nicholas Midzi; Masceline Jenipher Mutsaka-Makuvaza; Isaac Phiri; Karen Palatio; Didier Bakajika; Honorat M. Zouré; Elizabeth Juma; Molly Anderson; Rebecca Mwabvu; Moses J. Bockarie; Jorge Cano; Sammy M. Njenga (International Journal of Infectious Diseases)
Objectives: Zimbabwe is endemic for lymphatic filariasis (LF) with 39 districts identified for mass drug administration (MDA) in 2014. The objective of this study was to reassess the current population requiring MDA. Methods: The LF confirmatory mapping method was used to evaluate the prevalence of circulating filarial antigens among school-aged children (9-14 years) in previously endemic districts. This was achieved through a cross-sectional survey between 2021 and 2023, applying a cluster sampling approach across 39 districts, targeting 18,720 children to assess ongoing LF transmission. Results: The findings revealed a significant decline in LF prevalence, with an overall rate of 0.43%. Importantly, 82.05% of districts previously identified as endemic were reclassified as nonendemic. Only seven districts retained endemic status, necessitating continued MDA using the triple-drug therapy regimen. Population estimates based on 2022 census data indicated that 1.19 million individuals across these districts require MDA, representing an 84.4% reduction compared to previous estimates. Despite the progress, the persistence of low-level transmission in certain districts highlights the need for sustained surveillance and morbidity management services, including hydrocele surgery and lymphedema care. Conclusion: There was a significant reduction in the number of people requiring MDA. The decline in LF endemicity is attributed to a combination of factors, including prior rounds of MDA and vector control initiatives including historical interventions, such as dichlorodiphenyltrichloroethane spraying against human African trypanosomiasis.